Peran Kader Kesehatan dalam Meningkatkan Cakupan Pelayanan Kesehatan Ibu dan Anak di Wilayah Pedesaan - Wadi, Hamzan; Maksum, Lalu (Lembaga Penelitian dan Pendidikan, 2026)
Maternal and child health (MCH) services in rural areas continue to face various challenges, including limited access to health facilities, low utilization of services, and the influence of socio-cultural factors. In this context, community health cadres play a strategic role as a bridge between the formal health system and the community. This study aims to analyze the role of health cadres in increasing the coverage of maternal and child health services in Janapria Village, Central Lombok Regency. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis involving health cadres, village midwives, and pregnant women as well as mothers of children under five. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of the roles, strategies, and challenges faced by health cadres in delivering MCH services. The results indicate that health cadres play an active role in registering pregnant women and children under five, implementing posyandu activities, providing health education, conducting home visits, and reminding mothers of scheduled MCH services. These roles contribute significantly to increased community participation in utilizing maternal and child health services. The social and cultural approaches adopted by health cadres, including interpersonal communication and the use of local social networks, enhance community trust and acceptance of health services. Nevertheless, several challenges were identified, such as limited training opportunities, inadequate supervision, high workload, and insufficient incentives for health cadres. The discussion highlights that the effectiveness of health cadres in improving MCH service coverage is strongly influenced by their integration into the formal health system and the availability of sustainable policy support. Health cadres function not only as technical implementers but also as agents of behavioral change within rural communities. This study concludes that strengthening the role of health cadres is a crucial strategy for improving maternal and child health service coverage in rural areas. Therefore, policy support focusing on capacity building, continuous supervision, and adequate incentives is essential to ensure the sustainability and effectiveness of health cadre programs.